Pediatric small bowel transplantation: A single-center experience from Turkey - Tuğmen, Cem; Baran, Maşallah; Sert, İsmail and Anıl, Ayşe Berna and Kebapçı, Eyüp and Doğan, Sait Murat and Kılınç, Selçuk and Aydın, Gaye and Diniz, Ayşe Gülden and Ölmez, Mustafa and et al. (Turkish Journal of Gastroenterology, 2016)
Abstract Background/Aims: Small bowel transplantation (SBTx) is a treatment option for patients with serious parenteral nutrition-related problems in intestinal failure. İzmir Tepecik Training Research Hospital Organ Transplantation Center is still the only pediatric intestinal transplant center in Turkey. Materials and Methods: This study was approved by the local ethics committee. Patients’ data were analyzed from the medical charts and the hospital digital database. Seven isolated SBTxs were performed in six children between 2010 and 2016. Results: One jejunal segment and six partial jejuno-ileal segments were used for seven transplants. All grafts were retrieved from deceased donors (one child and six adult donors). The six recipients had a mean age of 8.8±6.9 years (9 months to 17 years; M: 4, F: 2). The mean follow-up period of patients was 727±848 (34 to 1950) days. Acute cellular rejection (ACR) rates were 57% (n: 4) in the first 2 months. Graft loss due to severe ACR was seen in one patient. Central line-associated fungal (n: 3, 42%) and bacterial infections (n: 3, 42%) were seen in the first 2 months. Two Epstein-Barr virus (EBV) infections were recorded between 3 and 8 months in two patients. Our 1-year patient and graft survival rates were 71% and 71%, respectively. Conclusion: SBTx has become a treatment modality for patients with intestinal failures. Management of ACR and infections are still challenging problems in SBTx. Appropriate-sized cadaveric donors are very limited in Turkey for pediatric intestinal transplantation candidates. Although the number of SBTxs performed was small, this study shows promising results.